A Comprehensive Review of Nanoemulsion Applications and their Recent Advancements - Das, Prativa; Panda, Jnyana R.; Patro, Ch Niranjan; Sahu, Baby; Patnaik, Soumya Stuti (Current Nanomaterials, 2023)
Background: Nanoemulsions are submicron-sized suspensions that are being studied extensively as pharmacological vehicles for enhancing the outcomes of drug delivery. Nanoemulsions are isotropic thermodynamic systems in which two immiscible liquids (water and oil) are combined to form a single phase using pertinent surfactants. Nano-emulsions are resilient to sedimentation or creaming due to their nano-droplet size. Ostwald ripening represents the principal process accountable for the disintegration of nanoemulsion. Droplet diameters in nanoemulsions typically range from 20 to 500 nanometers. The diameter and surface parameters of nanoemulsion droplets play are of paramount significance in determining the bioactivity of the formulation. Nanoemulsion offers a promising future in various industries like cosmetology, diagnosis, pharmacological regimens, and biomedicine in the future. Methods: Pharmaceutical surfactants are utilized to synthesize nanoemulsions, which are Generally Regarded As Safe (GRAS). The stability of the NEs against coalescence mainly depends on the type and concentration of the surfactant employed. Nanoemulsions are formulated from a variety of oils, notably natural, semi-synthetic, and synthetic oils. Results: Over the past decade, various patents and clinical research have exemplified the applications of the NE system. Their application as a drug delivery entity in the ophthalmic, topical, transdermal, intranasal, intravenous, and oral routes is widely appreciated. Also, they have gained remarkable importance in the cosmetic industry. Conclusion: This review presents the importance of various components of NE and their importance in droplet formation and provides a brief insight into various drug administration routes of NE.
Keywords: ocular drug delivery